A Study of Theory of Mind in Paranoid Schizophrenia: A Theory or Many Theories? - Scherzer, Peter B.; Léveillé, Edith; Achim, André; Boisseau, Émilie; Stip, Emmanuel (Frontiers in Psychology, 2012)
Social cognitive psychologists (Frith, 1992; Hardy-Baylé et al, 2003) sought to explain the social problems and clarify the clinical picture of schizophrenia by proposing a model that relates many of the symptoms to a problem of metarepresentation i.e. theory of mind (ToM). Given the differences in clinical samples and results between studies, and considering the wide range of what is considered to constitute ToM, the question is, is there a core function, or is ToM multifaceted with dissociable facets? If there are dissociable dimensions or facets which are affected in patients with paranoid schizophrenia? To answer these questions, a group of 21 individuals diagnosed with paranoid schizophrenia and 29 non-clinical control subjects, were tested on a battery of five different measures of theory of mind. The results confirmed that there was little difference in specificity of three of the tests in distinguishing between the clinical and non-clinical group, but there were important differences in the shared variance between the tests. Further analyses hint at two dimensions although a single factor with the same variance and the same contributing weights in both groups could explain the results. The deficits related to the attribution of cognitive and affective states to others inferred from available verbal and non-verbal information. Further analyses revealed incorrect attributions of mental states including the attribution of threatening intentions to others non-interpretative responses and incomplete answers, depending on the test of theory of mind.